Exploration of Five Flaccidities in Medical Formulae Investigations of Flaccidity - Qing LIN; Guangwen WU (康复学报)
Medical Formulae Investigations is a comprehensive prescription monograph which is composed of pathology, methodology, formula and herbs. In the part of the monograph related to flaccidity, the etiology, pathogenesis, prescription and methodology of"five flaccidities"which are closely connected with diseases of heart, lung, liver and kidney have been described in detail. The authors in this article explore the characteristics of pathology, methodology, formula and herbs of"lung flaccidity", "pulse flaccidity", "tendon flaccidity", "bone flaccidity"and"atrophy flaccidity". Based on them, the roles of spleen and stomach in the treatment of"five flaccidities"are also discussed so as to provide theoretical evidence for clinical treatment and recovery of the related diseases.